Dynamic object representations in infants with and without fragile X syndrome - Farzin, Faraz; Rivera, Susan M. (Frontiers in Human Neuroscience, 2010)
Our visual world is dynamic in nature. The ability to encode, mentally represent, and track an object’s identity as it moves across time and space is critical for integrating and maintaining a complete and coherent view of the world. Here we investigated dynamic object processing in typically developing (TD) infants and infants with fragile X syndrome (FXS), a single-gene disorder associated with deficits in dorsal stream functioning. We used the violation of expectation method to assess infants’ visual response to expected versus unexpected outcomes following a brief dynamic (dorsal stream) or static (ventral stream) occlusion event. Consistent with previous reports of deficits in dorsal stream-mediated functioning in individuals with this disorder, these results reveal that, compared to mental age-matched TD infants, infants with FXS could maintain the identity of static, but not dynamic, object information during occlusion. These findings are the first to experimentally evaluate visual object processing skills in infants with FXS, and further support the hypothesis of dorsal stream difficulties in infants with this developmental disorder.